Comparison of three pulpotomy agents in primary molars: a randomised clinical trial - Elham Farrokh Gisoure (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2011)
INTRODUCTION: Pulpotomy is an accepted treatment for the management of cariously exposed pulps in symptom free primary molars. The purpose of this study was to compare the clinical and radiological outcomes of three different single-visit vital pulp therapies including pulpotomy with electrosurgery (ES), formocresol (FC) and ferric sulfate (FS) in cariously exposed primary molar teeth. MATERIALS & METHODS: Seventy-six patients, 5-10 years old, were enrolled in this clinical investigation. One primary molar tooth of each patient was selected for this study. Samples were randomly divided into three groups. Teeth were treated with FC in group 1 (i.e. control group) (n=24), FS in group 2 (n=28), and ES in group 3 (n=24) using standardized pulpotomy procedures. All treated teeth were clinically and radiographically evaluated after 6 and 9 months. Statistical analysis was performed using Fishers exact test. RESULTS: The overall success rate in groups 1, 2 and 3 was 87.5%, 82.1% and 83.3%, respectively. Favorable clinical and radiological success rates of FS and ES pulpotomy was observed which was comparable to FC. CONCLUSION: FS and ES can be considered alternative materials for the pulpotomy of primary molars.